(untitled) (Polifonia, 2002)
ABSTRACT: This article attempts to draw some data about the profile of the teacher of English in Brazilian public schools. We interviewed 11 teachers. They revealed that there is a shortage of “real teachers” in the state of Mato Grosso. Most teachers are what they call “pseudo-teachers”. These are teachers who do not have a degree in English, know very little of English, and teach English to fill in their required time schedule. They belief students do not learn English at public schools and point out several reasons for that such as: large classes, meager resources, no time available to allocate time to study, low salary, mismatch between theory and practice. This situation reflects and reinforces the devalued status of English language among other disciplines in the curriculum of public schools.